How to do Process Tracing: A Method for Testing “How Change Happened” in Complex and Dynamic Settings - Lynn, Jewlya; Stachowiak, Sarah; Beyers, Jennifer (ORS Impact, 2022)
Process tracing is a causal methodology that can help people understan d how a particular large-scale change actually happened within a compl ex dynamic environment. Much of the existing literature provides impor tant information about the method; we wrote this brief to help more pe ople operationalize the concepts and learn about practical steps for u sing this method more easily, with quality, and toward a more equitabl e world. This piece was written based on our experiences implementing process tracing when our experience showed that existing materials on the method had a lot more conceptual than practical information. We’ve approached this as people with some successful (and some unsuccessful ) experience with the method itself, alongside deep experience in eval uating initiatives and strategies in complex and dynamic settings. We focus not on the Bayesian side of process tracing but rather on how th is can be implemented in a way that’s more participatory and lifts up the experiences and wisdom of those closest to the work and the proble ms being tackled. We hope this contributes to and helps make more appr oachable the important work of political scientists and methodologists upon which this work sits.